Effects of Multifunctional Margins Implementation on Biodiversity in Annual Crops - Manuel Moreno-García (MDPI AG, 2021)
The most suitable land for agricultural use has been gradually occupied by crops around the world. Large, uninterrupted croplands have been created, while disproportionate amounts of fertilizers, insecticides, fungicides and herbicides are applied on them. As a result, agricultural activity has a negative impact on biodiversity the ecological intensification of cultivated lands has become necessary. Multifunctional Margins (MFM), the establishment of native flora margins adjacent to croplands, provide a semi-natural habitat for food and wildlife refuge. Three different species mixtures sown in MFM were studied in this paper. The large capacity of six species used in MFM (Borago officinalis, Glebionis coronaria, Coriandrum sativum, Sinapis alba, Trifolium resupinatum and Vicia sativa) was determined. Reductions of up to 65% in the appearance of weeds and increases of 36% in pollinator biodiversity in sown MFM with respect to the MFM of spontaneous flora were observed. The biodiversity of the epigeal fauna increased by 15% in the MFM of spontaneous flora and by 32% in sown MFM, with respect to annual crops.